Modulation of Hippocampal Neuroplasticity by Fas/CD95 Regulatory Protein 2 (Faim2) in the Course of Bacterial Meningitis. Issue 1 (January 2014) - Tauber, Simone C.; Harms, Kristian; Falkenburger, Born; Weis, Joachim; Sellhaus, Bernd; Nau, Roland; Schulz, Jorg B.; Reich, Arno
Abstract: Fas-apoptotic inhibitory molecule 2 (Faim2) is a neuron-specific membrane protein and a member of the evolutionary conserved lifeguard apoptosis regulatory gene family. Its neuroprotective effect in acute neurological diseases has been demonstrated in an in vivo model of focal cerebral ischemia. Here we show that Faim2 is physiologically expressed in the human brain with a changing pattern in cases of infectious meningoencephalitis. In Faim2-deficient mice, there was increased caspase-associated hippocampal apoptotic cell death and an increased extracellular signal-regulated kinase pattern during acute bacterial meningitis induced by subarachnoid infection with Streptococcus pneumoniae type 3 strain. However, after rescuing the animals by antibiotic treatment, Faim2 deficiency led to increased hippocampal neurogenesis at 7 weeks after infection. This was associated with improved performance of Faim2-deficient mice compared to wild-type littermates in the Morris water maze, a paradigm for hippocampal spatial learning and memory. Thus, Faim2 deficiency aggravated degenerative processes in the acute phase but induced regenerative processes in the repair phase of a mouse model of pneumococcal meningitis. Hence, time-dependent modulation of neuroplasticity by Faim2 may offer a new therapeutic approach for reducing hippocampal neuronal cell death and improving cognitive deficits after bacterial meningitis.